2020
DOI: 10.1038/s41467-019-14204-z
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-wide antitermination mechanism sustaining identity of embryonic stem cells

Abstract: Eukaryotic gene expression relies on extensive crosstalk between transcription and RNA processing. Changes in this composite regulation network may provide an important means for shaping cell type-specific transcriptomes. Here we show that the RNA-associated protein Srrt/Ars2 sustains embryonic stem cell (ESC) identity by preventing premature termination of numerous transcripts at cryptic cleavage/polyadenylation sites in first introns. Srrt interacts with the nuclear cap-binding complex and facilitates recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…Another type of transcripts that we and other teams observed in hen2-2 and se-2 plants are truncated or misprocessed transcripts spanning the first intron ( 14 , 15 , 35 , 68 ). Similar 5′ transcript derived from protein coding genes have also been observed in human cells depleted from ARS2 and result from premature transcription termination rather than from compromised splicing of full-length pre-mRNAs ( 19 , 34 , 69 ). However, both SE and ARS2 do interact with splicing factors.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Another type of transcripts that we and other teams observed in hen2-2 and se-2 plants are truncated or misprocessed transcripts spanning the first intron ( 14 , 15 , 35 , 68 ). Similar 5′ transcript derived from protein coding genes have also been observed in human cells depleted from ARS2 and result from premature transcription termination rather than from compromised splicing of full-length pre-mRNAs ( 19 , 34 , 69 ). However, both SE and ARS2 do interact with splicing factors.…”
Section: Discussionmentioning
confidence: 53%
“…Among the proteins that co-purify with FLAG-SE, both HOS5 and CPL1 have been implicated in splicing ( 56 ), and a previous study detected several auxiliary factors of the U1 snRNP as SE interactants ( 11 ). A very recent study suggests that the ARS2-mediated recruitment of U1 snRNP to 5′ proximal pre-mRNA sequences favours splicing and full-length transcription, and disfavours premature transcription and degradation ( 69 ). Hence, the increased accumulation of truncated or mis-spliced transcripts in se-2 hen2-2 double mutants may also be explained by a dual role of SE in recruiting either splicing factors or NEXT.…”
Section: Discussionmentioning
confidence: 99%
“…Another type of transcripts that we and other teams observed in hen2-2 and se-2 plants are truncated or misprocessed transcripts spanning the first intron (14,15,35,68). Similar 5′ transcript derived from protein coding genes have also been observed in human cells depleted from ARS2 and result from premature transcription termination rather than from compromised splicing of full-length pre-mRNAs (19,34,69). However, both SE and ARS2 do interact with splicing factors.…”
Section: Discussionmentioning
confidence: 53%
“…Among the proteins that co-purify with FLAG-SE, both HOS5 and CPL1 have been implicated in splicing (56), and a previous study detected several auxiliary factors of the U1 snRNP as SE interactants (70). A very recent study suggests that the ARS2-mediated recruitment of U1 snRNP to 5′ proximal pre-mRNA sequences favours splicing and full-length transcription, and disfavours premature transcription and degradation (69). Hence, the increased accumulation of truncated or mis-spliced transcripts in se-2 hen2-2 double mutants may also be explained by a dual role of SE in recruiting either splicing factors or NEXT.…”
Section: Discussionmentioning
confidence: 99%
“…While the 5′ end of Xist does not harbor obvious U1 snRNA binding sites (66), we and others have found that Repeat A associates with protein components of the U1 and other snRNPs ( Supplementary Table S3; (7,16,21)). Moreover, several proteins that were identified as Xist cofactors in recent genetic and proteomic screens -namely NXF1, SRRT, and SCAF4 -have known roles in suppressing premature cleavage and polyadenylation (10,21,26,(67)(68)(69). Future work will determine whether these proteins or others mediate Xist's antiterminator activity.…”
Section: Discussionmentioning
confidence: 99%